Comparative analysis of Escherichia coli contamination on fresh produce at the market: human handling is a significant parameter of contamination - Güran, Mümtaz; Şanlitürk , Gİzem; Hadid, Zoubida; Hadid, Karima; Aksay, Bİrsu; Rahhal, Muhammad; Ayman, Nareen; Alhrasshir, Joudi; Akçay, Nİmet İlke (Progress in Nutrition, 2021)
This study explores the effect of human handling on E. coli contamination of fresh produce (FP) in the overlooked market stage where customers touch FP. Study includes an observational and a comparative part with 3 experimental sample groups as; (i) Control group (CG), (ii) Touched FP group (TG) and (iii) FP touched with gloves group (GG). In the comparative part, generic E. coli and STEC were screened, quantified and analyzed for antibiotic susceptibilities. The average score of sellers’ knowledge level was low (39%).  E. coli counts from banana, lettuce, carrot and tomato were found to be significantly higher (p=0.037, p=0.046, p=0.046 and p=0.034 respectively) in TG compared to CG which indicates human handling as a significant factor of bacterial contamination in the market. E. coli counts were significantly lower for banana, lettuce and tomato in GG (p=0.037, p=0.001, p=0.034 respectively) which is probative for the dissemination at the market through human handling and is also indicating this as a useful/practical prevention tool. Shiga toxin-producing E. coli (STEC-O157:H7) was isolated only from one lettuce sample in TG. The highest resistance rate was observed for ampicillin (44%), followed by cephalothin (40%), tetracycline (24%) and amoxicillin-clavulanic (24%).  Here, we demonstrate that human handling of FP in the market stage is a significant factor on E. coli contamination which may include STEC. Furthermore, our findings suggest that, this contamination is preventable by using gloves or similar practical materials.